A Relationship between Spiritual Intelligence and Psychological Capital with Academic Performance among Students in Kashan University of Medical Sciences in 2016 - Hamid Rahimi (Zanjan University of Medical Sciences and Health Services, 2018)
Background and objectives: Spiritual intelligence and psychological capital are an approach that help ones to adapt with environment, health, performance and creativity. Therefore, the purpose of this research was analysis of relationship between spiritual intelligence and psychological capital academic performance among students in Kashan University of Medical Sciences. Martials and methods: The type of research was correlative descriptive. The statistical population consisted of students of Kashan University of Medical Sciences that 294 students were selected by stratified random sampling. The data collection tool was a spiritual intelligence questionnaire in 40 items and a psychological capital inventory questionnaire in 24 items with five degrees Likert scale. The validity of the contents of tools was verified. Reliability was estimated by Cronbach's alpha coefficient for spiritual intelligence 0.82 and psychological capital of 0.91. Data analysis was done at descriptive and inferential level using SPSS software version 22. Results: The findings showed that means of spiritual intelligence components (3.20±0.50) and psychological capital (3.51±0.41) were higher than average (3). Also there are significant and positive relation between spiritual intelligence with academic performance (r=0.25) and psychological capital with academic performance (r=0.19). Conclusion: According to the findings, spiritual intelligence and higher psychological capital were associated with better academic performance. By improving the dimensions of spiritual intelligence and psychological capital, it is possible to improve the academic performance of students.